In-line near-infrared spectroscopy for the characterization of dispersion in polymer-clay nanocomposites - Barbas, J. M. (2012)
In-line Near-Infrared spectroscopy (NIR) is used to monitor clay dispersion in the polymer matrix during the preparation of polymer nanocomposites by melt-mixing in a batch mixer. Based on chemometrics principles, various single parameter calibration models employing data obtained from widely used nanocomposite dispersion characterization techniques are developed and their quality tested. Given the generally unsatisfactory outcome, multi-parameter calibration models are then assessed, a 7-parameter model encompassing factors derived from oscillatory rheometry, FT-IR and thermomechanical data yielding good results. Since the validity of the model outside the material/equipment/ operating boundaries that were used to generate it was shown to be quite restricted, a second 7-parameter model is derived from a broader set of experimental data. Finally, the model is successfully applied to monitor in real time the evolution of clay dispersion with mixing time.